2021
DOI: 10.3390/rs13214326
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Climate Change and Human Activities on NDVI Changes in China

Abstract: The spatiotemporal evolution of vegetation and its influencing factors can be used to explore the relationships among vegetation, climate change, and human activities, which are of great importance for guiding scientific management of regional ecological environments. In recent years, remote sensing technology has been widely used in dynamic monitoring of vegetation. In this study, the normalized difference vegetation index (NDVI) and standardized precipitation–evapotranspiration index (SPEI) from 1998 to 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 90 publications
(98 reference statements)
7
29
0
Order By: Relevance
“…The NDVI in northeastern East Asia showed an increasing trend during 1982-2014, which is consistent with the study of Sun et al (2021) [60] and Liu et al (2021) [61], and we further found a significant change in NDVI growth rate in northern East Asia around 1998, showing a trend of slowing down during 1998-2014. It has been shown that NDVI changes are closely related to temperature and precipitation [62].…”
Section: Discussionsupporting
confidence: 92%
“…The NDVI in northeastern East Asia showed an increasing trend during 1982-2014, which is consistent with the study of Sun et al (2021) [60] and Liu et al (2021) [61], and we further found a significant change in NDVI growth rate in northern East Asia around 1998, showing a trend of slowing down during 1998-2014. It has been shown that NDVI changes are closely related to temperature and precipitation [62].…”
Section: Discussionsupporting
confidence: 92%
“…China is located on the northwest coast of Asia and the Pacific Ocean, spanning latitude 3.51-53.34°N and longitude 73.29°E-135.04°E [89]. It is the third largest country in the world, with a land area of approximately 9.6 million square kilometers [13,91]. China has many different types of topography, with terrain that is higher in the west and lower in the east, featuring a three ladder-like distribution [92].…”
Section: Study Domainmentioning
confidence: 99%
“…The SPEI is a drought index that reflects water deficit at different timescales [28], which is suitable for drought monitoring and analysis in the context of climate change [56]. Based on climatic water balance, the SPEI considers the impact of water budget changes, between precipitation and PET (i.e., amount of transpiration and evaporation under sufficient water), on drought behavior [4,91]. The Th model [94] was used to account for the PET effect in this study, due to the simplicity of the calculation process and the accessibility of basic data.…”
Section: Standardized Precipitation Evapotranspiration Indexmentioning
confidence: 99%
“…However, the regions above 3,800 m are mainly located in the northwest of Maqu County, where some literatures indicate that the region is vulnerable to climatic effects (Wu et al, 2019;Yang et al, 2021). In addition, soil water-salt is more sensitive at lower elevations than at higher elevations, probably because lower elevations are more susceptible to human activities (Liu et al, 2021). Therefore, the specific intrinsic mechanism need to be further explored.…”
Section: Influence Of Topography On Soil Water-saltmentioning
confidence: 99%